Increasing water productivity with improved N fertilizer management - Nangia, Vinay; Turral, Hugh; David, S. (Springer, 2008)
There is continuing debate about the role of water productivity and the potential to increase it in response to significantly increased water demand to meet the future needs for food?estimated to be roughly double that of today by 2050. The debate centers round the relative potential benefits of enhancing rainfed agriculture, improving irrigation and expanding areas of both. All expansion and intensification options will require significantly more water to be used, often in places where the ecosystem impacts of agriculture are already severe. Improvement in water productivity can result from improving the provision and management of the other factor inputs of crop production. There is considerable debate on the ability of other inputs?typically nitrogen?to substitute for water. This paper describes a set of simulations undertaken with well calibrated maize (Zea mays L.) crop model in Decision Support System for Agro-technology Transfer (DSSAT). The simulations investigate the response to nitrogen under rainfed conditions in Florida, and show that neither the transpiration ratio nor the harvest index are constant in practice, and that fertilizer use can enhance water productivity, even in quite high yield conditions and that the transpiration ratio can be increased by N fertilizer application at low levels of crop water use.